Pengaruh Pendidikan Kewirauasahaan Dan Kreativitas Terhadap Minat Berwirausaha Dengan Efikasi Diri Sebagai Variabel Intervering Pada Studi Mahasiswa Kewirausahaan Universitas Negeri Makassar - Ilham Abu; Marhawati Marhawati; Alfira Alfira; Alda Ananda; Andi Amrullah; Arjuna Agung Grison Masiku (CV. Sakura Digital Nusantara, 2023)
This study aims to determine the direct and indirect influence of entrepreneurship education and creativity on entrepreneurial interests through self-efficacy in students majoring in entrepreneurship class of 2022, Makassar State University. The research method used in this research is quantitative. The population in this study is all students of the class of 2022 at Makassar State University for the 2022/2023 Academic Year which amounts to 105 students with a sample of 41 students. Based on the results of the research that has been carried out, this research can be a source of information or reference for teaching staff or lecturers to be biased in directing and guiding students related to the development of entrepreneurial interests, students are expected to deepen their interest in business management so that they are not focused on the knowledge produced, but also able to do business ventures and develop them. For further research, efforts will be made to deepen and expand this research both in terms of variables and the development of research methods.